2013
DOI: 10.1186/1477-7827-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M stimulates cell migration and proliferation by down-regulating E-cadherin in HTR8/SVneo cell line through STAT3 activation

Abstract: BackgroundDuring the first trimester of pregnancy, trophoblastic E-cadherin expression is down-regulated, thereby allowing extravillous trophoblasts (EVTs) to acquire the potential for migration and invasiveness. The aim of the present study was to investigate the role of OSM on the migration and proliferation of EVT cell line HTR8/SVneo with regard to its effects on the expression of E-cadherin and STAT3 activation.MethodsWe investigated the effects of OSM on RNA and protein expression of E-cadherin by real t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Our results found that IL-27 could decrease the phosphorylation of STAT1, STAT3 and STAT5 during EMT. This is consistent with research done by Ko et al which previoulsy validated that activation of STAT3 could lead to decreased expression of E-cadherin [ 26 ]. Our results suggest that the JAK/STAT signalling pathway might be a key molecular mechanism of IL-27 activity in pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results found that IL-27 could decrease the phosphorylation of STAT1, STAT3 and STAT5 during EMT. This is consistent with research done by Ko et al which previoulsy validated that activation of STAT3 could lead to decreased expression of E-cadherin [ 26 ]. Our results suggest that the JAK/STAT signalling pathway might be a key molecular mechanism of IL-27 activity in pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Transfection of HTR8/SVneo cells with 25 nM STAT3-specific siRNA (and not scrambled siRNA) significantly decreased the amount of STAT3 and phosphorylated STAT3, as shown in the previous study. 9 Transfection of HTR8/SVneo cells with STAT3 siRNA also significantly decreased the expression of MMP-2 and MMP-9 that was increased by OSM ( p <0.05 for both), without affecting expression of the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) protein ( Fig. 1C and D ).…”
Section: Resultsmentioning
confidence: 90%
“…The activation of STAT3 by OSM was confirmed in a previous study. 9 The cells were treated with OSM (20 ng/mL) for 48 h with or without pretreatment with the STAT3 inhibitor, stattic (Tocris, R&D system, Minneapolis, MN, USA), at 0.5 µM or 1 µM for 1 h in dimethyl sulfoxide (DMSO) and subjected to Western blotting as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrated that the inhibition of STAT3 phosphorylation resulted in the suppression of proliferation, migration, invasion and increased apoptosis of HTR-8/SVneo cells 31 32 33 . Certain cytokines and other molecules enhance HTR-8/SVneo cell invasion through STAT3 phosphorylation 34 35 36 .…”
Section: Discussionmentioning
confidence: 99%